На каждый день: учение о жизни, изложенных в изречениях / редактор Н. Н. Гусев - Толстой Лев Николаевич (1992)
Вых. дан. ориг.: М.: Гослитиздат, 1929 Экземпляры: КХ (20111015) / Инвентарный номер: 1010468 / Сис.шифр: Р1 / Авт.знак: Т 53 / ГРНТИ: 17 / ББК: 84(2=411.2)-4